Sparse multi-stage regularized feature learning for robust face recognition. Issue 1 (January 2015) - Borgi, Mohamed Anouar; Labate, Demetrio; El Arbi, Maher; Ben Amar, Chokri
Highlights A new feature-extraction approach for efficient FR based on directional features. An augmented multi-stage or multi-regularization convex optimization. Results on various face databases demonstrate the effectiveness of our approach. The approach presents a trade-off between recognition and computational complexity. Three protocol experimental are tested among them the SSPP.